Negative transfer and english writing proficiency among junior middle school students in China - Xiaofang Zhao; Esther Jawing; Xiaoman. Liu (Global Academic Excellence, 2024)
English and Chinese exhibit notable differences across various linguistic aspects. Hypotaxis is a significant feature emphasized in English, whereas parataxis holds prominence in Chinese. Proficiency in writing is a crucial skill to acquire in English language learning, involving the mastery of vocabulary, syntax, and grammar. Chinese students often encounter challenges in comprehending these concepts, resulting in inevitable errors in their written compositions. Such errors can be attributed to the negative transfer effect stemming from their mother tongue (i.e. Chinese). Negative transfer from Chinese may impede or disrupt the acquisition of a second language. Furthermore, the stark sociocultural disparities between Chinese and Western cultures lead to the inadvertent application of Chinese language rules in English expression, consequently compromising accurate usage. This paper utilizes language negative transfer theory, alongside comparative and error analysis theories, to analyze how mother tongue negative transfer affects the English writing proficiency of junior middle school students. Specifically, the study examines the influence of negative transfer on grammar, vocabulary, and discourse. Data for this investigation is collected through the analysis of composition materials. Additionally, the paper concludes by offering recommendations to mitigate the adverse effects of mother tongue negative transfer on English writing proficiency, with the goal of improving English language instruction for Chinese students.